Forest understory vegetation is more related to soil than to climate towards the cold distribution margin of European beech. (31st May 2019) - Weigel, Robert; Gilles, Jennifer; Klisz, Marcin; Manthey, Michael; Kreyling, Juergen
Abstract: Question: It is debated whether forest understory communities will be sensitive to projected climate change or inert due to the regulating effect of local site conditions and soil parameters. A distinction between the relative importance of climate or soil is often hardly possible because both factors usually change at different spatial scales in forests. Here, we compare the relative influence of climate and soil on the forest understory vegetation in lowland beech forest ecosystems ( Fagus sylvatica ), which were selected for their ecological homogeneity. Location: Nine sites along a strong temperature gradient (Δ T = 4 K from east to west in winter, south to north in summer) between Rostock (Germany) and Gdańsk (Poland) in a Baltic Quaternary ground moraine landscape. Methods: We conducted a vegetation survey in 55 vegetation plots (80 m 2 each) across nine forest sites mono‐dominated by European beech and analysed how much variation in understory plant composition is explained by climate and soil parameters. Results: Soil explained 32% of the compositional variation of understory vegetation across sites, climate 22%, and their interaction 14%. Topsoil pH, subsoil organic matter content, and subsoil C/N ratio were the most important soil variables; growing season temperature and annual water availability were the most important climatic variables. Conclusion: The strong dependence on soil properties could moderate the response of the forest understory vegetation to projected climate change. Forest soil properties, however, also depend on the dominant tree species and the macroclimate. To predict climate change impacts on forest understory vegetation, climate change assessments should consider indirect climate change effects as well as interactions between climate and soil. Abstract : In European lowland beech forests, soil explained 32% of the compositional variation of understory vegetation across sites, climate 22%, and their interaction 14%. The stronger dependence on soil properties could moderate the response of the forest understory vegetation to projected climate change. Future climate change assessments should also account for interactions between climate and soil.